2019
DOI: 10.2337/dci19-0001
|View full text |Cite
|
Sign up to set email alerts
|

The TCF7L2 Locus: A Genetic Window Into the Pathogenesis of Type 1 and Type 2 Diabetes

Abstract: Over the past ∼15 years there has been great progress in our understanding of the genetics of both type 1 diabetes and type 2 diabetes. This has been driven principally by genome-wide association studies (GWAS) in increasingly larger sample sizes, where many distinct loci have now been reported for both traits. One of the loci that dominates these studies is the TCF7L2 locus for type 2 diabetes. This genetic signal has been leveraged to explore multiple aspects of disease risk, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 51 publications
0
41
0
2
Order By: Relevance
“…The potential relationship between obesity-induced inflammation and autoimmune disease, including islet autoimmunity, could also underlie our previous observations that the type 2 diabetesassociated TCF7L2 genetic variant, which may be involved in fatty acid metabolism (39), accelerates antigen spreading in individuals with a single positive ICA512/IA-2 or insulin autoantibody who are obese or overweight (40). In this smaller study of pediatric and adult TrialNet participants who had available ImmunoChip data, the effect of ceBMI or age strata was not evaluated.…”
Section: Discussionmentioning
confidence: 73%
“…The potential relationship between obesity-induced inflammation and autoimmune disease, including islet autoimmunity, could also underlie our previous observations that the type 2 diabetesassociated TCF7L2 genetic variant, which may be involved in fatty acid metabolism (39), accelerates antigen spreading in individuals with a single positive ICA512/IA-2 or insulin autoantibody who are obese or overweight (40). In this smaller study of pediatric and adult TrialNet participants who had available ImmunoChip data, the effect of ceBMI or age strata was not evaluated.…”
Section: Discussionmentioning
confidence: 73%
“…In the current study, long-term weight gain of participants modified the effects of nut consumption on the MetS risk, based on rs12255372 and rs7903146 polymorphisms of the TCF7L2 gene, suggesting an interplay of BMI and genetic susceptibility on the association of nut consumption and MetS incidence. The effect of TCF7L2 variants on risk of type 2 diabetes and obesity as well as modulation effect of BMI on the association between diabetes and TCF7L2 variants, have been controversial [ 26 , 27 , 43 ]. This discrepancy, at least in part, may be attributed to the extent of linkage disequilibrium in different population [ 8 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…84,103,129,130 However, there are an increasing molecular evidence that emphasized on the role of some variants in coding regions as causative genes that associated with T2D. 112,131,132 The sibling-relative risk for T2D is 3 compared with 15 for T1D. 84,133 Genetic studies revealed the concordance of T2D in monozygotic twins is about 70% to 90%, while it is only 20% to 30% in dizygotic twins.…”
Section: Genetics and Architecture Of T2dmentioning
confidence: 99%
“…So far, many susceptibility and predisposition genetic loci have been described and found to be influenced by other environmental factors such as obesity and life style effects 84,103,129,130 . However, there are an increasing molecular evidence that emphasized on the role of some variants in coding regions as causative genes that associated with T2D 112,131,132 …”
Section: Overview Of T2dmentioning
confidence: 99%